Joshua, Judges and Ruth - Gray, John (London, UK Thomas Nelson, 1967)
Includes index.
Keywords: Bible. O.T. Joshua -- commentaries; Bible. O.T. Judges -- commentaries; Bible. O.T. Ruth -- commentaries